The perceived value and positioning of coaching in a leadership development programme within a state-owned entity - Herbert, Samantha Lynn (My University, 2022)
Organisations around the world are embattled in the corporate race to secure highly skilled talent to stay ahead of the human resources recruitment curve. Additionally, many top performing employees within organisations also need to be stimulated to remain at the top of the skills curve and ultimately, to serve their organisations. The format of such stimulation is often undertaken by organisations in the form of leadership development programmes. Most leadership development programmes employ coaching as a self-development tool with the intention of perpetual learning through positive change. The common understanding is that coaching contributes to the performance of organisations. It has however, been found that coaching on its own cannot withstand the responsibility of determining organisational wellness, which motivated this study to research the value-add which coaching contributes to leadership development programmes and to explore whether such value–add is partial to the positioning of coaching in the development programmes. The purpose of this study is to suggest best practices for the positioning of coaching in corporate leadership development programmes, to derive optimal value for organisations. The data was collated through a thematic analysis of information drawn from semi-structured interviews. The study drew largely from the personal experiences of graduates from a leadership development programme within a State-Owned Entity in the logistics fraternity. Executive level employees were interviewed for senior levels of work experience. The key finding of this study is that coaching must be included in the strategy phase of planning within an organisation for purposes of alignment of all stakeholders, for high levels of leadership support and ultimately, for the creation of environments conducive for effective coaching. When coaching is strategically dealt with, the contribution of this study enables organisations to obviate probable downstream failure of coaching practices through the aligned buy-in of organisations from the highest levels of leadership and it provides a road map for effective placement of coaching in future leadership development programmes. Coaching is most effective when supported by various fundamentals, in this case, by its positioning within leadership development programmes for optimal value extraction.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Management in Business and Executive Coaching to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, 2022
Keywords: Value of Coaching; Shift; Leadership Development Programmes; Learning; UCTD; SDG-8: Decent work and economic growth